2021
DOI: 10.1186/s12957-020-02118-w
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of enlarged paraaortic lymph nodes detected during left-sided colorectal cancer surgery: a single-center retrospective cohort study

Abstract: Background Very few studies have been conducted on the treatment strategy for enlarged paraaortic lymph nodes (PALNs) incidentally detected during surgery. The purpose of this study was to investigate the benefit of lymph node dissection in patients with incidentally detected enlarged PALNs. Methods We retrospectively reviewed patients with left colon and rectal cancer who underwent surgical resection with PALN dissection between January 2010 and D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Previous studies have applied different criteria based on either size and/or morphology for identifying LNM [ 22 24 ]. Another study used the radiographic criteria of lymph node diameter (> 1.0 cm) or round shape, heterogeneity, eccentricity, hilar thinning, calcification, central necrosis, and perinodal infiltration to evaluate lymph node involvement with sensitivity of 54-88%, specificity of 55-66%, accuracy of 61-70% [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have applied different criteria based on either size and/or morphology for identifying LNM [ 22 24 ]. Another study used the radiographic criteria of lymph node diameter (> 1.0 cm) or round shape, heterogeneity, eccentricity, hilar thinning, calcification, central necrosis, and perinodal infiltration to evaluate lymph node involvement with sensitivity of 54-88%, specificity of 55-66%, accuracy of 61-70% [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies included in this meta-analysis were cohort studies, and one was conducted by Lee [ 20 ], which included 263 patients with left colon or rectal cancer who underwent para-aortic lymph node dissection (PALND). A total of 19 (7.2%) patients with PALNM confirmed by routine postoperative pathology, of whom 9 underwent R0 resection and 10 underwent R2 resection.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have found tumour stage (Duke’s or TNM classes) crucial in predicting survival outcomes [ 54 , 55 ], it is still considered inconclusive probably because many CRC patients usually present at the late stage of the disease when the severity has become intense with a less success rate of treatment outcome. Instead, several studies reported these factors: tumour staging and location as potentially significant predictors of treatment outcome but not definitive prognosis factors [ 56 , 57 , 58 ]. The latter studies reported a reverse trend, indicating that tumour stage and grade have been lowered in most outcomes, pointing to the uncertain predictive potential of tumour stage and grade.…”
Section: Discussionmentioning
confidence: 99%
“…The latter studies reported a reverse trend, indicating that tumour stage and grade have been lowered in most outcomes, pointing to the uncertain predictive potential of tumour stage and grade. Lee, Park [ 57 ] reported that higher clinical T and N stages were not predictive factors for pathologic CRC in the multivariate analysis. The present study could not portray a tumour site as a significant predictor of survival status, even though [ 44 ] reported a tumour in the rectum to be a significant predictor of survival status in their multivariable technique.…”
Section: Discussionmentioning
confidence: 99%